2020
DOI: 10.1194/jlr.ra120001121
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miRNA-23a-3p promotes atherogenesis in a novel mouse model of atherosclerosis

Abstract: Of the known regulators of atherosclerosis, miRNAs have been demonstrated to play critical roles in lipoprotein homeostasis and plaque formation. Here, we generated a novel animal model of atherosclerosis by knocking-in LDLRW483X in C57BL/6 mice, as the W483X mutation in LDLR is considered the most common, newly identified pathogenic mutation in Chinese familial hypercholesterolemia (FH) individuals. Using the new in vivo mouse model combined with a well-established atherosclerotic in vitro human cell model, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
(65 reference statements)
1
6
0
Order By: Relevance
“…These newly observed interactions were not previously linked to cHL pathogenesis. However, Guo et al observed recently, using in vivo mouse and in vitro human cell models, that has-miR-23a-3p regulates inflammation and apoptosis by interacting with TNFAIP3 in atherosclerosis [37]. In line, this was the strongest interaction observed in our reporter assay experiments, suggesting that overexpression of this miRNA is an alternative and most probably a more subtle mechanism to the recurrent loss of function genomic alterations targeting TNFAIP3 in cHL [17].…”
Section: Discussionsupporting
confidence: 69%
“…These newly observed interactions were not previously linked to cHL pathogenesis. However, Guo et al observed recently, using in vivo mouse and in vitro human cell models, that has-miR-23a-3p regulates inflammation and apoptosis by interacting with TNFAIP3 in atherosclerosis [37]. In line, this was the strongest interaction observed in our reporter assay experiments, suggesting that overexpression of this miRNA is an alternative and most probably a more subtle mechanism to the recurrent loss of function genomic alterations targeting TNFAIP3 in cHL [17].…”
Section: Discussionsupporting
confidence: 69%
“…The miR-23 cluster is highly expressed in EC and has been implicated in processes supporting angiogenesis ( 58 60 ). MiR-23 has also been implicated in atherogenesis, potentially by supporting a proinflammatory secretome in HCAEC ( 61 ) and has been linked to cardiomyopathy in mice ( 62 ). miR-126 has been implicated in the promotion of angiogenesis, however, numerous additional functions have also been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Gene‐set enrichment analysis (GSEA, https://www.gsea-msigdb.org/gsea/index.jsp) of the signaling pathways was performed as described by LC‐Bio (https://www.lc-bio.cn/). Publicly available transcriptome data GSE94044 (Mohanta et al , 2022b; Data ref: Mohanta et al , 2022a) and GSE137581 (Guo et al , 2020b; Data ref: Guo et al , 2020a) were acquired from the Gene Expression Omnibus database (https://www.ncbi.nlm.nih.gov/geo/). DEGs were selected with fold change > 2 or fold change < 0.5 and P ‐value < 0.05, using GEO2R.…”
Section: Methodsmentioning
confidence: 99%